Pañjābī loka sāhita ate maddhakālī kāwi - Ghummaṇa, Bikarama Siṅgha (Ammritasara : Rūhī Prakāshana, 1994)
Articles on Panjabi folk literature and medieval Panjabi poetry.
In Panjabi.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Panjabi poetry -- 1500-1800 -- History and criticism; Folk literature, Panjabi -- History and criticism